Ac2-26 Alleviates Brain Injury after Cardiac Arrest and Cardiopulmonary Resuscitation in Rats via the eNOS Pathway - Jing Gong; Qi-Hang Tai; Guang-Xiao Xu; Xue-Ting Wang; Jing-Li Zhu; Xiao-Qing Zhao; Hai-Bin Sun; Dan Zhu; Wei Gao (Hindawi Limited, 2020)
Background. Brain injury is the leading cause of death following cardiac arrest (CA) and cardiopulmonary resuscitation (CPR). Ac2-26 and endothelial nitric oxide synthase (eNOS) have been shown to reduce neuroinflammation. This study is aimed at determining the mechanism by which Ac2-26 protects against inflammation during brain injury following CA and CPR. Methods. Sixty-four rats were randomized into sham, saline, Ac2-26, and Ac2-26+L-NIO (endothelial nitric oxide synthase (eNOS) inhibitor) groups. Rats received Ac2-26, Ac2-26+L-NIO, or saline after CPR. Neurologic function was assessed at baseline, 24, and 72 hours after CPR. At 72 hours after resuscitation, serum and brain tissues were collected. Results. Blood-brain barrier (BBB) permeability increased, and the number of surviving neurons and neurological function decreased in the saline group compared to the sham group. Anti-inflammatory and proinflammatory factors, neuron-specific enolase (NSE) levels, and the expression of eNOS, phosphorylated (p)-eNOS, inducible nitric oxide synthase (iNOS), and oxidative stress-related factors in the three CA groups significantly increased (P<0.05). BBB permeability decreased, and the number of surviving neurons and neurological function increased in the Ac2-26 group compared to the saline group (P<0.05). Ac2-26 increased anti-inflammatory and reduced proinflammatory markers, raised NSE levels, increased the expression of eNOS and p-eNOS, and reduced the expression of iNOS and oxidative stress-related factors compared to the saline group (P<0.05). The effect of Ac2-26 on brain injury was reversed by L-NIO (P<0.05). Conclusions. Ac2-26 reduced brain injury after CPR by inhibiting oxidative stress and neuroinflammation and protecting the BBB. The therapeutic effect of Ac2-26 on brain injury was largely dependent on the eNOS pathway.